The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1063/1.361797
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study on structural and dielectric properties of lead zirconate titanate/(Pb,La)(Zr(1−x)Ti(x))O3 thin films deposited by metallo-organic decomposition technology

Abstract: Articles you may be interested inAn investigation on the leakage current and time dependent dielectric breakdown of ferroelectric lead-zirconate-titanate thin film capacitors for memory device applications Pin-hole free ferroelectric ͑Pb,La͒͑Zr 1Ϫx Ti x ͒O 3 thin films with uniform composition have been fabricated using the metallo-organic precursor compounds, which were carefully home synthesized. The structural development, spectroscopic, and dielectric properties of these films have been systematically inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 45 publications
(37 reference statements)
2
17
1
1
Order By: Relevance
“…These peaks are well known and have been identified as E͑2TO͒, B I + E, A I ͑2TO͒, and A I ͑3TO͒, respectively. 22 The results of this figure also show that increasing P O 2 results in appreciable changes in the spectral lines. These changes mainly occur in the relative intensity of all modes.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…These peaks are well known and have been identified as E͑2TO͒, B I + E, A I ͑2TO͒, and A I ͑3TO͒, respectively. 22 The results of this figure also show that increasing P O 2 results in appreciable changes in the spectral lines. These changes mainly occur in the relative intensity of all modes.…”
Section: Resultsmentioning
confidence: 68%
“…The Zr/ TiO 6 metal-oxygen octahedral vibrational modes obtained through these measurements indicated changes in the crystal structure of the PZT perovskite phase due to increasing O 2 pressure. 22 Figure 2 displays the FT-IR spectra of the PZT/ Pt͑111͒ / Ti/ SiO 2 /Si͑100͒ films, whose backgrounds were corrected by a careful subtraction of the background arising from the substrate. The spectrum belonging to the film annealed in air ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Su superficie se muestra granular (figura 3b), con l-bulos submicromŽtricos de simetr'a radial caracter'sticos de la fase perovskita (22,23). La rugosidad superficial media del PLT es de 4 nm, lo que corresponde al 1.5% del espesor de la l ‡mina.…”
Section: Dep-sito De Heteroestructuras Plt/x N O M /(100)inpunclassified
“…Many methods such as pulsed laser ablation (PLD), rf sputtering, chemical vapor deposition (CVD), metal organic decomposition (MOD), sol-gel process and multiple electrophoretic deposition are used to prepare ferroelectric thin films [2][3][4][5][6][7] . MOD is one of the considerable deposition methods, since it is a non-gelling chemical process in which molecular homogeneity is attained in the liquid phase, and the solutions can be produced without solution gelling and at a lower processing temperature 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Many methods such as pulsed laser ablation (PLD), rf sputtering, chemical vapor deposition (CVD), metal organic decomposition (MOD), sol-gel process and multiple electrophoretic deposition are used to prepare ferroelectric thin films [2][3][4][5][6][7] . MOD is one of the considerable deposition methods, since it is a non-gelling chemical process in which molecular homogeneity is attained in the liquid phase, and the solutions can be produced without solution gelling and at a lower processing temperature 5 . Few reports have shown that the microstructural charactheristics and electrical properties of PZT thin films depend greatly on the annealing temperature 8 and film thickness [9][10][11] , however little has been done in regard to the dependence of ferroelectric properties and fracture toughness on annealing procedure.…”
Section: Introductionmentioning
confidence: 99%